Implmementasi Kurikulum Merdeka Berdasarkan Pendekatan Understanding by Design - Resa, Anggina (Jurnal Primary (Kajian Ilmu Pendidikan Dasar dan Humaniora), 2023)
During the pre-pandemic period, the Ministry of Education and Culture issued a policy on using the 2013 Curriculum and then the 2013 Curriculum was simplified into an emergency curriculum which made it easy for educational units to manage learning. The independent curriculum is the improvement and restoration of learning which will be launched for the first time in 2021. The independent curriculum includes mapping of competency standards, independent learning and a minimum competency assessment. The paradigm built strengthens the independence of the teacher as the holder of control in the learning process and strengthens the rights and abilities of students to determine the learning process so as to guarantee more flexibility for educators to formulate learning designs and assessments according to the characteristics and needs of students. The implementation of the independent curriculum is based on an understanding by design approach, the profile of Pancasila students plays a role as a guide that guides all policies and reforms in the Indonesian education system, including learning and assessment. This study used a qualitative approach with the research method of literature study where the researcher carried out a series of activities related to methods of collecting library data, reading and taking notes, and managing writing materials obtained from various sources and then obtained answers and conclusions.